JUDICIAL ACTIVISM AND THE IMPLEMENTATION OF FUNDAMENTAL RIGHTS: A REFLECTION ON THE CARELESS USE OF HERMENEUTICS IN THE FEDERAL CONSTITUTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The 21st century is marked by major transformations and changes in the scenario, many of which were conquered decades before, with the establishment of Democracy and the prediction of numerous fundamental rights in the Federal Constitution of 1988. However, this is not the only thing that stands out: there is an enormous legal role, that is, the Judiciary with more severe actions and even often with prerogatives of other powers. With the careless use of legal hermeneutics, the Courts have adopted more activist postures, presenting different interpretations of the constitutional texts, which constantly generates criticism of the phenomenon, mainly about the purpose in which it is guided: realization of fundamental rights. Thus, for the development, in addition to the works indicated by the professor, the method of systematic bibliographical research was used, through the search for journals, mainly “Jurisdiction and Judicial Activism: limits of the Judiciary’s performance”, by Clarissa Tassinari and “Theoretical Receptions Inadequates in Terra Brasilis”, by Lênio Luiz Streck. Finally, during the development of the work, the concept and origin of judicial activism and its conditioning relationship with the judicialization of politics, as well as its differentiations, were discussed. In the last chapter, the main criticisms of the phenomenon and the solution presented by Lenio Streck, with the Judicial Decision Theory, were presented.